The Perceval Sutureless Valve in Aortic Root Reoperation - (:unkn) unknown (My University, 2017)
The case is reported of a 62-year-old man with severe aortic regurgitation that was related to failed prior valve-sparing ascending aortic aneurysm repair, and who was successfully treated with a Perceval Sutureless valve.
Keywords: Humans; Middle Aged; Male; Reoperation; Aortic Valve; Aortic Valve Insufficiency; Prosthesis Failure; Aortic Aneurysm; Heart Valve Prosthesis; Sutureless Surgical Procedures